AN INQUIRY APPROACH TO FACILITATE REFLECTION IN ACTION RESEARCH FOR ESL PRE-SERVICE TEACHERS - Val Madin, Caroline; Swanto, Suyansah (TEFLIN Journal, 2019)
Reflection is a significant skill in action research, but many practitioners still display unsatisfactory reflective thinking levels, especially among teachers. Pre-service teachers, in particular, have voiced issues concerning their reflections in action research. Although reflections are personal and have infinite forms, research has demonstrated that using an inquiry approach can build reflection skills. This study aimed to identify pre-service teachers' and their respective lecturer-supervisors' views on the use of an inquiry approach to facilitate the reflection aspect in action research. A question-structured checklist was provided to the research participants to guide their reflection in action research. Data were collected from twenty (n=20) English as a Second Language (ESL) pre-service teachers and five (n=5) lecturer-supervisors in an Institute of Teacher Education Malaysia campus through follow-up interviews and focused group discussions. Findings revealed the benefits of the inquiry approach used in guiding the pre-service teachers' reflections in their action research and writing the final reports. Feedback from the lecturer-supervisors suggested that the use of the inquiry approach had guided the pre-service teachers' reflections to be more organized and relevant to the focus in each section in the report. Future recommendations on the application of an inquiry approach are suggested.